Sustainable Marketing Strategy and Marketing Success of ISO 14001 Certified Manufacturing Businesses in Thailand - Pimpan, Suparada; Ruaguttamanun, Chutima; Wongkhae, Komkrit (Journal of Humanities and Social Sciences Thonburi University, 2021)
The purpose of this research is to examine the influence of sustainable marketing strategy through the product creativity, customer acceptance and leads to marketing success. Data was collected from 208 ISO 14001 certified manufacturing businesses in Thailand. The questionnaire mail survey was used as research instrument. In this research, the structural equation model (SEM) was employed for the hypothesis testing. The results show that technology adaptation orientation and environmental process development have significant influences on marketing success. This study verifies the importance of sustainable marketing strategy as consistent with stakeholder theory. However, conclusion and discussion include directions for future research are discussed in the last section of this research.